Optical Film

By using acrylic resin with high glass transition temperature and a specific type of ultraviolet absorber in the optical film, the contradiction between bending resistance and ultraviolet shielding of the optical film in the foldable display is solved, and multiple performance optimization of the optical film is achieved.

CN119775700APending Publication Date: 2025-04-08KANEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411358905.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When applying an optical film to a foldable display, there is a contradiction between the bending resistance of the optical film and the UV shielding: in order to improve bending resistance, the optical film needs to be thinned, but this will reduce the UV shielding; in order to improve the UV shielding, the amount of UV absorber needs to be added, but this will reduce the film making operation.

Method used

An optical film containing an acrylic resin having a glass transition temperature of 120°C or higher and a specific type of ultraviolet absorber is used. The content of the ultraviolet absorber is between 1.1 and 2.0 parts by weight, and has a triazine skeleton and a tri(hydroxyphenyl)triazine skeleton, a molecular weight between 500 and 800, and the maximum absorbance wavelength in the ultraviolet visible absorption spectrum is 350 nm or more.

Benefits of technology

It achieves excellent bending resistance, film making workability and ultraviolet shielding of optical films, and is suitable for flexible displays such as foldable displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064413800000021
    Figure BDA0005064413800000021
  • Figure BDA0005064413800000061
    Figure BDA0005064413800000061
  • Figure BDA0005064413800000071
    Figure BDA0005064413800000071
Patent Text Reader

Abstract

Provided is an optical film, comprising an acrylic resin having a glass transition temperature of 120° C. or higher and an ultraviolet absorber, wherein the content of the ultraviolet absorber relative to 100 parts by weight of the acrylic resin is 1.1 parts by weight or higher and 2.0 parts by weight or lower, the ultraviolet absorber has a triazine skeleton, a molecular weight of 500 or higher and 800 or lower, a wavelength at which the absorbance in the ultraviolet-visible absorption spectrum becomes maximum is 350 nm or higher, the absorbance of light of a wavelength of 380 nm of the optical film is 1.0 or higher and 2.0 or lower, and the thickness is 15 μm or higher and 30 μm or lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to optical films. Background Art

[0002] Acrylic resins have excellent transparency, color tone, appearance, heat resistance, and processability, and are therefore suitable for use in, for example, optical films, which are used in, for example, organic EL displays (see, for example, Patent Document 1).

[0003] On the other hand, organic EL displays are used as foldable displays in applications such as smartphones.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-88728 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] Here, when the optical film is applied to a foldable display, in order to improve the bending resistance of the optical film, for example, it is considered to make the optical film thinner, but if the optical film is thinner, the ultraviolet shielding property of the optical film is reduced, and as a result, the durability of the foldable display is reduced. Therefore, in order to improve the ultraviolet shielding property of the optical film, it is necessary to increase the amount of ultraviolet absorber added, but if the amount of ultraviolet absorber added is increased, the film-making workability of the optical film is reduced.

[0009] An object of the present invention is to provide an optical film having excellent bending resistance, film-forming workability, and ultraviolet shielding properties.

[0010] Solutions for solving problems

[0011] [1] An optical film comprising an acrylic resin having a glass transition temperature of 120°C or higher and a UV absorber, wherein the content of the UV absorber is 1.1 parts by weight or higher and 2.0 parts by weight or lower relative to 100 parts by weight of the acrylic resin, the UV absorber has a triazine skeleton, a molecular weight of 500 or higher and 800 or lower, and a wavelength at which the absorbance in the UV-visible absorption spectrum becomes maximum is 350 nm or higher, the optical film has an absorbance of light of a wavelength of 380 nm of 1.0 or higher and 2.0 or lower, and a thickness of 15 μm or higher and 30 μm or lower.

[0012] [2] The optical film according to [1], wherein the ultraviolet absorber has a tris(hydroxyphenyl)triazine skeleton.

[0013] [3] An optical film comprising an acrylic resin having a glass transition temperature of 120°C or higher, and a UV absorber, wherein the content of the UV absorber is 1.1 parts by weight or higher and 2.0 parts by weight or lower relative to 100 parts by weight of the acrylic resin, the UV absorber has a tris(hydroxyphenyl)triazine skeleton and a molecular weight of 500 to 800, the optical film having an absorbance of light of a wavelength of 380 nm of 1.0 to 2.0 and a thickness of 15 μm to 30 μm.

[0014] [4] The optical film according to any one of [1] to [3], wherein the acrylic resin has a ring structure in the main chain.

[0015] [5] The optical film according to [4], wherein the ring structure is one or more selected from the group consisting of a glutarimide ring, a lactone ring, a maleic anhydride ring, a maleimide ring, and a glutaric anhydride ring.

[0016] [6] The optical film according to [5], wherein the acrylic resin has a structural unit represented by the following formula (1).

[0017]

[0018] (Where R 1 and R 2 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.

[0019] [7] The optical film according to any one of [1] to [3], wherein the content of methyl methacrylate units in the acrylic resin is 98% by weight or more, and the syndiotacticity in terms of triads is 55% or more.

[0020] [8] The optical film according to [7], wherein the syndiotacticity of the acrylic resin in terms of triads is 55% or more and 70% or less.

[0021] [9] The optical film according to any one of [1] to [8], which is a biaxially stretched film.

[0022]

[10] A flexible display comprising the optical film according to any one of [1] to [9].

[0023]

[11] An acrylic resin composition comprising an acrylic resin having a glass transition temperature of 120° C. or higher and a UV absorber, wherein the acrylic resin has a methyl methacrylate unit content of 98% by weight or higher and a syndiotacticity in terms of triads of 55% or higher,

[0024] The content of the ultraviolet absorber is 1.1 parts by weight or more and 2.0 parts by weight or less relative to 100 parts by weight of the acrylic resin. The ultraviolet absorber has a tris(hydroxyphenyl)triazine skeleton, a molecular weight of 500 to 800, and a wavelength at which the absorbance in the ultraviolet-visible absorption spectrum becomes maximum is 350 nm or more.

[0025]

[12] The acrylic resin composition according to

[11] , which is in the form of pellets.

[0026] Effects of the Invention

[0027] According to the present invention, an optical film having excellent bending resistance, film forming workability, and ultraviolet shielding properties can be provided. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present invention will be described.

[0029] (Optical Film)

[0030] The optical film of the present embodiment includes an acrylic resin having a glass transition temperature of 120° C. or higher and a UV absorber.

[0031] In this specification and claims, acrylic resin refers to a polymer of a monomer having an acryloyl group and / or a monomer having a methacryloyl group. In this case, the acrylic resin may be any of a homopolymer and a copolymer. When the acrylic resin is a copolymer, the acrylic resin may be a copolymer of a monomer having no acryloyl group or methacryloyl group.

[0032] The content of the ultraviolet absorber relative to 100 parts by weight of acrylic resin is 1.1 parts by weight or more and 2.0 parts by weight or less, preferably 1.2 parts by weight or more and 1.8 parts by weight or less, and more preferably 1.3 parts by weight or more and 1.5 parts by weight or less. If the content of the ultraviolet absorber relative to 100 parts by weight of acrylic resin is 1.1 parts by weight, the ultraviolet shielding property of the optical film of the present embodiment is improved, and if it is 2.0 parts by weight or less, the film-making workability of the optical film of the present embodiment is improved.

[0033] The ultraviolet absorber is a compound having a triazine skeleton and a wavelength of 350nm or more at which the absorbance in the ultraviolet visible absorption spectrum becomes the maximum, or a compound having a tris(hydroxyphenyl)triazine skeleton. Here, the tris(hydroxyphenyl)triazine skeleton refers to a skeleton in which the three carbon atoms constituting the triazine skeleton are substituted by three hydroxyphenyl groups. It should be noted that the ultraviolet absorber can be a compound having a tris(hydroxyphenyl)triazine skeleton and a wavelength of 350nm or more at which the absorbance in the ultraviolet visible absorption spectrum becomes the maximum.

[0034] When the wavelength at which the absorbance in the ultraviolet-visible absorption spectrum of the ultraviolet absorber having a triazine skeleton becomes maximum is 350 nm or more, the ultraviolet shielding property of the optical film of this embodiment is improved. It should be noted that the wavelength at which the absorbance in the ultraviolet-visible absorption spectrum of the ultraviolet absorber becomes maximum is, for example, 365 nm or less.

[0035] If the ultraviolet light absorber has a tris (hydroxyphenyl) triazine skeleton, the ultraviolet light shielding property of the optical film of the present embodiment is improved. Here, the hydroxyphenyl group can be substituted by a substituent other than the hydroxyl group. As a substituent other than the hydroxyl group, as long as it is a group that does not adversely affect the ultraviolet light shielding property of the optical film of the present embodiment, it is not particularly limited, and for example, an alkyl group with a carbon number of more than 1 and less than 2, an alkoxy group with a carbon number of more than 4 and less than 6, and two or more kinds of substituents can also be used in combination.

[0036] The molecular weight of the ultraviolet absorber is 500 to 800, preferably 550 to 750, and more preferably 570 to 720. If the molecular weight of the ultraviolet absorber is 500 or more, the film-forming workability of the optical film of the present embodiment is improved, and if it is 800 or less, the ultraviolet shielding property of the optical film of the present embodiment is improved.

[0037] It should be noted that, when the optical film of the present embodiment includes a mixture of ultraviolet absorbers, that is, a compound having a triazine skeleton and a wavelength of 350nm or more at which the absorbance in the ultraviolet visible absorption spectrum becomes the maximum, or a mixture of compounds having a tris(hydroxyphenyl)triazine skeleton, the molecular weight of the main component of the mixture of ultraviolet absorbers can be within the above range, and the average molecular weight of the mixture of ultraviolet absorbers is preferably within the above range. Here, the main component of the mixture of ultraviolet absorbers refers to the component with the largest content in the mixture of ultraviolet absorbers.

[0038] Specific examples of the ultraviolet absorber include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine and 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine. Commercially available products of the ultraviolet absorber include LA-F70 (manufactured by ADEKA).

[0039] The 1% weight loss temperature of the ultraviolet absorber is preferably 330° C. or higher, more preferably 335° C. or higher, and further preferably 350° C. or higher. When the 1% weight loss temperature of the ultraviolet absorber is 330° C. or higher, the film forming workability of the optical film of the present embodiment is improved. The 1% weight loss temperature of the ultraviolet absorber is, for example, 500° C. or lower.

[0040] The 5% weight loss temperature of the ultraviolet absorber is preferably 330° C. or higher, more preferably 350° C. or higher, further preferably 380° C. or higher, and particularly preferably 400° C. or higher. When the 5% weight loss temperature of the ultraviolet absorber is 330° C. or higher, the film-forming workability of the optical film of the present embodiment is improved. The 5% weight loss temperature of the ultraviolet absorber is, for example, 500° C. or lower.

[0041] The absorbance of light of wavelength 380nm of the optical film of this embodiment is 1.0 or more and 2.0 or less, preferably 1.2 or more and 1.8 or less. When the absorbance of light of wavelength 380nm of the optical film of this embodiment is 1.0 or more, the ultraviolet shielding property of the optical film of this embodiment is improved, and when it is 2.0 or less, the film-making workability of the optical film of this embodiment is improved.

[0042] In addition, the transmittance of the light of wavelength 380nm of the optical film of the present embodiment is 1.0% or more and 10% or less, preferably 2.0% or more and 9.0% or less. When the transmittance of the light of wavelength 380nm of the optical film of the present embodiment is 1.0% or more, the film-making workability of the optical film of the present embodiment is improved, and when it is 10% or less, the ultraviolet shielding property of the optical film of the present embodiment is improved.

[0043] The thickness of the optical film of the present embodiment is 15 μm or more and 30 μm or less, preferably 17 μm or more and 27 μm or less, and more preferably 18 μm or more and 25 μm or less. When the thickness of the optical film of the present embodiment is 15 μm or more, the ultraviolet shielding property of the optical film of the present embodiment is improved, and when it is 30 μm or less, the bending resistance of the optical film of the present embodiment is improved.

[0044] The optical film of this embodiment can be applied to flexible displays such as foldable displays, bendable displays, rollable displays, and slidable displays. Specific examples of flexible displays include organic EL displays.

[0045] (Acrylic resin)

[0046] The glass transition temperature of the acrylic resin is 120°C or higher, preferably higher than 120°C, more preferably 121°C or higher, further preferably 123°C or higher, and further more preferably 125°C or higher. When the glass transition temperature of the acrylic resin is 120°C or higher, the dimensional change in a high temperature environment becomes small, so it is practically preferred. It should be noted that the glass transition temperature of the acrylic resin is, for example, 150°C or lower.

[0047] The acrylic resin is not particularly limited as long as the glass transition temperature is 120° C. or higher, and examples thereof include an acrylic resin (A1) having a ring structure in the main chain; or an acrylic resin (A2) having a methyl methacrylate unit content of 98% by weight or higher and a syndiotacticity of 55% or higher in terms of triad.

[0048] Here, the ring structure is preferably one or more selected from the group consisting of a glutarimide ring, a lactone ring, a maleic anhydride ring, a maleimide ring, and a glutaric anhydride ring.

[0049] (Acrylic resin (A1) having a ring structure in the main chain)

[0050] The acrylic resin (A1) having a glutarimide ring in the main chain has, for example, a structural unit represented by the following formula (1) as a structural unit having a ring structure in the main chain.

[0051]

[0052] (Where R 1 and R 2 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.

[0053] The acrylic resin (A1) having the structural unit represented by the formula (1) can be produced by a known method. An example of a method for producing the acrylic resin (A1) having the structural unit represented by the formula (1) is described below.

[0054] First, a twin-screw extruder equipped with a die at the outlet is used to melt a methyl methacrylate resin, and then an imidizing agent is injected to imidize the methyl methacrylate resin. Then, the strands extruded from the die are cooled in a water tank and pelletized using a pelletizer to obtain an acrylic resin (A1) having a structural unit represented by formula (1).

[0055] Examples of the imidizing agent include ammonia and a primary amine represented by the following formula (2). Among them, monomethylamine is preferred.

[0056] R 3 NH2(2)

[0057] (Where R 3 Same as formula (1).

[0058] The acrylic resin (A1) having a lactone ring in the main chain can be obtained by, for example, polymerizing a monomer represented by the following formula (3) and then subjecting the polymer to a heat treatment to form a lactone ring.

[0059]

[0060] (Where R 4 and R 5 Each is independently a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.)

[0061] Examples of the monomer represented by formula (3) include methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, and tert-butyl 2-(hydroxymethyl)acrylate, and two or more monomers may be used in combination. Among them, methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate are preferred, and methyl 2-(hydroxymethyl)acrylate is particularly preferred.

[0062] The content of the structural unit having a ring structure in the main chain in the acrylic resin (A1) is not particularly limited, and is, for example, 1% by weight or more and 40% by weight or less.

[0063] The acrylic resin (A1) may further have a structural unit derived from a (meth)acrylate. Examples of (meth)acrylates include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate; aryl (meth)acrylates such as phenyl (meth)acrylate; aryl (meth)acrylates such as benzyl (meth)acrylate; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, and the like, and two or more thereof may be used in combination. Among them, alkyl methacrylates are preferred, and methyl methacrylate is particularly preferred.

[0064] The acrylic resin (A1) may further have a structural unit derived from other monomers. Examples of the other monomers include, but are not particularly limited to, aromatic monomers such as styrene and methylstyrene; and nitrile monomers such as acrylonitrile and methacrylonitrile.

[0065] As the acrylic resin (A1) having a maleic anhydride ring in the main chain, for example, styrene-N-phenylmaleimide-maleic anhydride copolymer can be cited. As the acrylic resin (A1) having a maleimide ring in the main chain, for example, olefin-maleimide copolymers described in Japanese Patent Publication No. 2004-45893 can be cited. As the acrylic resin (A1) having a glutaric anhydride ring in the main chain, for example, heat-resistant copolymers described in Japanese Patent Publication No. 2003-137937 can be cited.

[0066] (Acrylic resin (A2) having a methyl methacrylate unit content of 98% by weight or more and a syndiotacticity of 55% or more in terms of triad)

[0067] The content of methyl methacrylate units in the acrylic resin (A2) is 98% by weight or more, preferably 99% by weight or more, and more preferably 100% by weight. When the content of methyl methacrylate units in the acrylic resin (A2) is 98% by weight or more, the chemical recyclability of the acrylic resin (A2) is improved.

[0068] The syndiotacticity of the acrylic resin (A2) calculated on a triad basis is 55% or more, preferably 56% or more, and more preferably 57% or more. If the syndiotacticity of the acrylic resin (A2) calculated on a triad basis is 55% or more, the glass transition temperature of the acrylic resin (A2) increases, and there is a tendency for the heat resistance to be improved. In addition, if the syndiotacticity of the acrylic resin (A2) calculated on a triad basis is 55% or more, there is a tendency for the solvent resistance of the obtained molded body to be improved, and the water vapor permeability to be reduced. There is no particular upper limit on the syndiotacticity of the acrylic resin (A2) calculated on a triad basis, but from the viewpoint of the molding temperature, the toughness of the molded body, and the secondary processability, it is preferably 70% or less, more preferably 67% or less, further preferably 65% ​​or less, and particularly preferably 63% or less.

[0069] The syndiotacticity of the acrylic resin (A2) in terms of triads is the ratio of chains of two structural units (diads) possessed by a chain of three consecutive structural units (triads) to be racemic (rr). It should be noted that in chains of structural units (diads) in polymer molecules, the same configuration is called meso, and the opposite configuration is called racemo, which are recorded as m and r, respectively.

[0070] As the synthesis method of acrylic resin (A2), it is not particularly limited, and examples thereof include anionic polymerization and free radical polymerization. Among them, from the viewpoint of environmental aspects, free radical polymerization is preferred (for example, with reference to International Publication No. 2023 / 238886). Here, the glass transition temperature of acrylic resin (A2) and the syndiotacticity in terms of triads can be controlled by the polymerization temperature of acrylic resin (A2). For example, by lowering the polymerization temperature of acrylic resin (A2), the glass transition temperature and syndiotacticity of acrylic resin (A2) increase. In addition, the glass transition temperature of acrylic resin (A2) can also be controlled by the molecular weight of acrylic resin (A2).

[0071] The monomers other than methyl methacrylate that can be used in the synthesis of the acrylic resin (A2) are not particularly limited, and examples thereof include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aryl acrylates such as phenyl acrylate; cycloalkyl acrylates such as cyclohexyl acrylate and norbornene acrylate; alkyl methacrylates other than methyl methacrylate such as ethyl methacrylate, propyl methacrylate, and butyl methacrylate; aryl methacrylates such as phenyl methacrylate; cycloalkyl methacrylates such as cyclohexyl methacrylate and norbornene methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; methacrylonitrile.

[0072] (Method for producing optical film)

[0073] The optical film of the present embodiment can be produced using a known method. An example of a method for producing the optical film of the present embodiment will be described below.

[0074] First, a twin-screw extruder equipped with a die head at the outlet is used to add an ultraviolet absorber to an acrylic resin and knead it. Then, the strands extruded from the die head are cooled in a water tank and pelletized by a granulator to obtain an acrylic resin composition. Next, a twin-screw extruder equipped with a T-die head at the outlet is used to melt the acrylic resin composition, and the sheet extruded from the T-die head is cooled by a cooling roller to obtain an original film. Next, the original film is biaxially stretched to obtain an optical film of this embodiment. At this time, the biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching.

[0075] When the glass transition temperature of the acrylic resin is set to Tg, the temperature when the original film is biaxially stretched is preferably above (Tg+5)°C and below (Tg+30)°C, more preferably above (Tg+6)°C and below (Tg+25)°C, and further preferably above (Tg+7)°C and below (Tg+20)°C. In addition, the surface ratio when the original film is biaxially stretched is not particularly limited, for example, it is 2 times or more and 10 times or less. The stretching speed when the original film is biaxially stretched is not particularly limited, for example, it is 1.1 times / minute or more and 100 times / minute or less. When the original film is biaxially stretched sequentially, the stretching speed in the first stage may be the same as or different from the stretching speed in the second stage. It should be noted that in the sequential biaxial stretching, usually, the stretching in the first stage is the stretching in the length direction (MD direction), and the stretching in the second stage is the stretching in the width direction (TD direction).

[0076] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment, and the said embodiment can be modified suitably within the range of the summary of this invention.

[0077] [Example]

[0078] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the examples.

[0079] (Glass transition temperature)

[0080] Using a high-sensitivity differential scanning calorimeter DSC7000X (manufactured by Hitachi High-Tech Science Corporation), 10 mg of the acrylic resin was heated at a heating rate of 10° C. / min in a nitrogen atmosphere, and the glass transition temperature was determined by a midpoint method.

[0081] (Polymerization conversion rate)

[0082] The polymerization conversion rate [%] was determined by the weight method from the ratio of the solid content weight of the polymerization solution to the weight of the monomers charged. At this time, the solid content weight of the polymerization solution was determined by drying the polymerization solution in an oven set at 150° C. for 30 minutes.

[0083] (syndiotacticity rr based on triad)

[0084] The acrylic resin was measured using a 400 MHz nuclear magnetic resonance apparatus AVANCE III (manufactured by Bruker) in a deuterated chloroform solution at 22°C and 16 cumulative times. 1 H-NMR spectrum. 1The area (X) of the region of 0.60 to 0.95 ppm and the area (Y) of the region of 0.60 to 1.25 ppm when tetramethylsilane (TMS) is set to 0 ppm are measured by H-NMR spectroscopy, and the formula:

[0085] (X / Y)×100

[0086] The syndiotacticity rr based on triads was calculated.

[0087] (The wavelength λ where the absorbance becomes maximum max )

[0088] The UV-visible absorption spectrum of the solution of the ultraviolet absorber was measured using a UV-visible spectrophotometer V-560 (manufactured by JASCO Corporation) to determine λ max .

[0089] (Absorbance and Transmittance)

[0090] The ultraviolet-visible absorption spectrum of the optical film was measured using an ultraviolet-visible spectrophotometer V-560 (manufactured by JASCO Corporation) to determine the absorbance and transmittance of light at a wavelength of 380 nm.

[0091] (1% and 5% weight reduction temperature)

[0092] Using a differential thermogravimetric simultaneous measuring apparatus STA7200 (manufactured by Hitachi High-Tech Science Corporation), 10 mg of the ultraviolet absorber was heated from room temperature at a heating rate of 10°C / min in a nitrogen atmosphere to determine 1% and 5% weight loss temperatures.

[0093] (Bending resistance)

[0094] After cutting out a sample of 25 mm × 130 mm from the optical film, a bending test was performed using a table-top durability tester DMLHB-FS-C (manufactured by YUASASYSTEM Co., Ltd.) at 23°C, 55% RH, a bending radius of 1.0 mm, and a bending speed of 60 times / min. At this time, the number of bends until the sample broke or cracks appeared in the sample was recorded to evaluate the bending resistance.

[0095] (Film-making workability)

[0096] During the film formation of the optical film, the film forming workability was evaluated by visually checking the contamination caused by the volatile components from the lip of the die head and the bleeding to the casting roll. The criteria for judging the film forming workability are as follows.

[0097] A: Casting roller is not contaminated

[0098] B: Part of the casting roll is contaminated

[0099] C: The entire surface of the casting roll is contaminated

[0100] (Example 1)

[0101] <Production of Acrylic Resin 1 Having a Ring Structure in the Main Chain>

[0102] The temperature setting of each temperature control zone of an intermeshing co-rotating twin-screw extruder (L / D=90) with a die head having a diameter of 40 mm at the outlet was set to 250-280°C, and the screw speed was set to 85 rpm, and the methyl methacrylate resin was melted and filled with a kneading block. Then, 1.8% by weight of monomethylamine (manufactured by Mitsubishi Gas Chemical Company, Inc.) was injected from the nozzle relative to the methyl methacrylate resin to imidize the methyl methacrylate resin. Then, the strands extruded from the die head were cooled in a water tank and pelletized by a pelletizer to obtain acrylic resin 1. The glass transition temperature of acrylic resin 1 is 125°C.

[0103] <Production of Acrylic Resin Composition>

[0104] The temperature setting of each temperature control zone of an intermeshing co-rotating twin-screw extruder (L / D=90) having a die head with a diameter of 40 mm at the outlet was set to 240-260° C., and the screw speed was set to 85 rpm. 1.4 parts by weight of an ultraviolet absorber LA-F70 (manufactured by ADEKA) (hereinafter referred to as UVA1) was added from a constant weight feeder with respect to 100 parts by weight of acrylic resin 1, and kneading was performed. Then, the strands extruded from the die head were cooled in a water tank and pelletized by a pelletizer to obtain an acrylic resin composition.

[0105] <Production of optical films>

[0106] After drying the acrylic resin composition at 100°C for 5 hours, the acrylic resin composition was melted using an intermeshing co-rotating twin-screw extruder (L / D=45) having a T-die with a diameter of 15 mm at the outlet. The sheet extruded from the T-die was then cooled using a casting roll to obtain an original film having a thickness of 80 μm.

[0107] The original film was simultaneously biaxially stretched using a film biaxial stretching apparatus IMC-1905 (manufactured by Imoto Seisakusho) at a temperature 15°C higher than the glass transition temperature of acrylic resin 1, with a stretching ratio of 2 in the longitudinal and transverse directions, to obtain an optical film having a thickness of 20 μm.

[0108] (Example 2)

[0109] An optical film was obtained in the same manner as in Example 1 except that 1.1 parts by weight of 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine (hereinafter referred to as UVA2) was added as a UV absorber based on 100 parts by weight of the acrylic resin.

[0110] (Example 3)

[0111] An optical film was obtained in the same manner as in Example 1 except that UVA2 was used as the ultraviolet absorber.

[0112] (Comparative Example 1)

[0113] An optical film was obtained in the same manner as in Example 1 except that the thickness of the original film was 160 μm and the thickness of the optical film was 40 μm.

[0114] (Comparative Example 2)

[0115] An optical film was obtained in the same manner as in Example 1 except that the thickness of the original film was 40 μm and the thickness of the optical film was 10 μm.

[0116] (Comparative Example 3)

[0117] An optical film was obtained in the same manner as in Comparative Example 2 except that 3.0 parts by weight of UVA1 was added to 100 parts by weight of acrylic resin 1.

[0118] (Comparative Example 4)

[0119] An optical film was obtained in the same manner as in Example 1 except that 0.7 parts by weight of UVA1 was added to 100 parts by weight of acrylic resin 1.

[0120] (Comparative Example 5)

[0121] An optical film was obtained in the same manner as in Example 1 except that 3 parts by weight of UVA1 was added to 100 parts by weight of acrylic resin 1.

[0122] (Comparative Example 6)

[0123] An optical film was obtained in the same manner as in Example 1 except that Tinuvin 477 (manufactured by BASF) (hereinafter referred to as UVA3) was used as the ultraviolet absorber.

[0124] (Comparative Example 7)

[0125] An optical film was obtained in the same manner as in Example 1 except that UVA3 was used as the ultraviolet absorber and 5 parts by weight was added to 100 parts by weight of the acrylic resin 1.

[0126] (Comparative Example 8)

[0127] An optical film was obtained in the same manner as in Example 1 except that Tinuvin 460 (manufactured by BASF) (hereinafter referred to as UVA4) was used as the ultraviolet absorber.

[0128] (Comparative Example 9)

[0129] An optical film was obtained in the same manner as in Example 1 except that UVA4 was used as the ultraviolet absorber and 5 parts by weight was added to 100 parts by weight of the acrylic resin 1.

[0130] (Comparative Example 10)

[0131] An optical film was obtained in the same manner as in Example 1 except that Tinuvin 479 (manufactured by BASF) (hereinafter referred to as UVA5) was used as the ultraviolet absorber.

[0132] (Example 4)

[0133] <Production of Acrylic Resin 2 Having a Methyl Methacrylate Unit Content of 98 wt % or More and a Syndiotacticity of 55 % or More in Triads>

[0134] 150 parts by weight of deionized water, 0.20 parts by weight of calcium phosphate as a dispersant, 0.0075 parts by weight of sodium α-olefin sulfonate, and 0.30 parts by weight of sodium chloride were added to a 4L glass reactor equipped with an H-type stirring blade type stirrer. Next, under a nitrogen atmosphere, 100 parts by weight of methyl methacrylate (MMA), 0.289 parts by weight of n-octyl mercaptan as a chain transfer agent, and 0.074 parts by weight of 2,2'-azobis(isobutyric acid) dimethyl ester V-601 (manufactured by FUJIFILM Wako Pure Chemical Corporation) as a polymerization initiator were added to the reactor while stirring at 250 rpm. The liquid temperature in the reactor was then raised to 70°C to initiate polymerization. At the moment of 2 hours from the initiation of polymerization, 0.10 parts by weight of calcium phosphate was added to the polymerization solution. At this time, an exothermic peak associated with the gel effect was observed at the moment of 4 hours and 20 minutes from the initiation of polymerization. The temperature was raised from the moment when 7 hours had passed since the initiation of polymerization, and the liquid temperature in the reactor was raised to 95°C. At the moment when 7 hours had passed since the initiation of polymerization, the polymerization conversion rate was 93%. After 2 hours from the moment when the liquid temperature in the reactor reached 95°C, the reactor was cooled to room temperature to terminate the polymerization, and a dispersion of acrylic resin was obtained. At this time, the polymerization conversion rate was 99%. Next, the dispersion of acrylic resin was washed with 1N hydrochloric acid in an amount of 0.1 times the amount of monomers added by weight, and then washed with water to remove the dispersant. Then, the acrylic resin washed with water was dehydrated and dried to obtain a bead-shaped acrylic resin 2. The glass transition temperature of acrylic resin 2 was 120°C, the content of MMA units was 100% by weight, and the syndiotacticity rr based on triads was 57%.

[0135] An optical film was obtained in the same manner as in Example 1 except that acrylic resin 2 was used in place of acrylic resin 1.

[0136] (Example 5)

[0137] An optical film was obtained in the same manner as in Example 2 except that acrylic resin 2 was used in place of acrylic resin 1.

[0138] (Example 6)

[0139] An optical film was obtained in the same manner as in Example 3 except that acrylic resin 2 was used in place of acrylic resin 1.

[0140] Tables 1 to 3 show the properties and evaluation results of the optical films of Examples 1 to 6 and Comparative Examples 1 to 10. Here, the amount of the ultraviolet absorber added refers to the amount added relative to 100 parts by weight of the acrylic resin.

[0141] [Table 1]

[0142]

[0143] [Table 2]

[0144]

[0145] [Table 3]

[0146]

[0147] Table 4 shows the properties of the ultraviolet absorber.

[0148] [Table 4]

[0149] UVA1 UVA2 UVA3 UVA4 UVA5 Number of hydroxyphenyl groups 3 3 3 2 1 Molecular weight 699 574 958 630 677 <![CDATA[λ max [nm]]]> 356 363 357 348 321 1% weight reduction temperature [℃] 395 335 317 346 337 5% weight reduction temperature [℃] 420 382 342 378 360

[0150] As can be seen from Tables 1 to 3, the optical films of Examples 1 to 6 have high bending resistance, film-forming workability, and ultraviolet shielding properties. In contrast, the thickness of the optical film of Comparative Example 1 is 40 μm, so the bending resistance is low. The thickness of the optical film of Comparative Example 2 is 10 μm, and the absorbance of light with a wavelength of 380 nm is 0.65 (transmittance is 22.4%), so the ultraviolet shielding property is low. The thickness of the optical film of Comparative Example 3 is 10 μm, but the amount of ultraviolet absorber added to 100 parts by weight of acrylic resin is 3.0 parts by weight, so the ultraviolet shielding property is high, but the film-forming workability is low. In the optical film of Comparative Example 4, the amount of ultraviolet absorber added to 100 parts by weight of acrylic resin is 0.7 parts by weight, and the absorbance of light with a wavelength of 380 nm is 0.65 (transmittance is 22.4%), so the ultraviolet shielding property is low. The optical film of Comparative Example 5 has low film-forming workability because the amount of ultraviolet absorber added is 3.0 parts by weight relative to 100 parts by weight of acrylic resin. The molecular weight of the ultraviolet absorber of the optical film of Comparative Example 6 is 958, and the absorbance of light with a wavelength of 380nm is 0.72 (transmittance is 19.1%), so the ultraviolet shielding property is low. In the optical films of Comparative Examples 7 and 9, the amount of ultraviolet absorber added is 5.0 parts by weight relative to 100 parts by weight of acrylic resin, so the film-forming workability is low. The optical film of Comparative Example 8 contains an ultraviolet absorber having two hydroxyphenyl groups, λ max The ultraviolet light shielding property of the optical film of Comparative Example 10 is low, because the absorbance of the light of wavelength 380 nm is 0.40 (transmittance is 39.8%). max The ultraviolet light absorber of 321 nm has an absorbance of 0.09 (transmittance of 81.3%) for light of wavelength 380 nm, and thus has low ultraviolet light shielding properties.

Claims

1. An optical film comprising an acrylic resin having a glass transition temperature of 120° C. or higher and a UV absorber, The content of the ultraviolet absorber is 1.1 parts by weight or more and 2.0 parts by weight or less relative to 100 parts by weight of the acrylic resin. The ultraviolet absorber has a triazine skeleton, a molecular weight of 500 to 800, and a wavelength at which the absorbance in the ultraviolet-visible absorption spectrum becomes maximum is 350 nm or more. The optical film has an absorbance of light of a wavelength of 380 nm of 1.0 or more and 2.0 or less, The thickness is 15 μm or more and 30 μm or less.

2. The optical film according to claim 1, wherein: The ultraviolet absorber has a tris(hydroxyphenyl)triazine skeleton.

3. An optical film comprising an acrylic resin having a glass transition temperature of 120° C. or higher and a UV absorber, The content of the ultraviolet absorber is 1.1 parts by weight or more and 2.0 parts by weight or less relative to 100 parts by weight of the acrylic resin. The ultraviolet absorber has a tris(hydroxyphenyl)triazine skeleton and a molecular weight of 500 or more and 800 or less. The optical film has an absorbance of light of a wavelength of 380 nm of 1.0 or more and 2.0 or less, The thickness is 15 μm or more and 30 μm or less.

4. The optical film according to any one of claims 1 to 3, wherein The acrylic resin has a ring structure in the main chain.

5. The optical film according to claim 4, wherein: The ring structure is one or more selected from the group consisting of a glutarimide ring, a lactone ring, a maleic anhydride ring, a maleimide ring, and a glutaric anhydride ring.

6. The optical film according to claim 5, wherein: The acrylic resin has a structural unit represented by the following formula (1): In the formula, R 1 and R 2 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, R 3 It is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms.

7. The optical film according to any one of claims 1 to 3, wherein The acrylic resin has a methyl methacrylate unit content of 98% by weight or more and a syndiotacticity in terms of triads of 55% or more.

8. The optical film according to claim 7, wherein: The acrylic resin has a syndiotacticity in terms of triads of 55% or more and 70% or less. 9 . The optical film according to claim 1 , which is a biaxially stretched film. 10 . A flexible display comprising the optical film according to claim 1 .

11. An acrylic resin composition comprising an acrylic resin having a glass transition temperature of 120° C. or higher and a UV absorber, The acrylic resin has a methyl methacrylate unit content of 98% by weight or more, a syndiotacticity in terms of triads of 55% or more, The content of the ultraviolet absorber is 1.1 parts by weight or more and 2.0 parts by weight or less relative to 100 parts by weight of the acrylic resin. The ultraviolet absorber has a tris(hydroxyphenyl)triazine skeleton, has a molecular weight of 500 to 800, and has a wavelength of 350 nm or more at which the absorbance in the ultraviolet-visible absorption spectrum reaches a maximum. 12 . The acrylic resin composition according to claim 11 , which is in the form of pellets.

Citation Information

Patent Citations

  • Heat-resistant copolymer and heat-resistant thermoplastic resin composition

    JP2003137937A

  • Transparent film, polarizer protection film, and polarizing plate

    JP2004045893A

  • Optical film, polarizing plate, and image display device

    JP2017088728A